Colibri and Caranguejo: genealogy and editing of two pioneering choros for guitar (Orfeu, 2021)
In the exclusive repertoire for guitar, with the exception of some works by Villa-Lobos, pieces for the instrument that refer to the period establishing choro as a musical genre, a process that spread from the mid-nineteenth century until the early twentieth century, are still rare and/or unknown. In an attempt to help fill this gap, the present article aims to present for the first time two choros for guitar composed around 1912: Colibri, by Melchior Cortez (1882-1947); and Caranguejo, by Francesco Rosa, the Gadanho (1872 -?). In examining reference works on the subject and through the survey of sources, editions and manuscripts unknown until then, the text has as secondary objectives to trace a preliminary genealogy of the works and their composers, to unravel the compositional relationship of the pieces (which can be played in solo or duo versions), discuss briefly some of the possible reasons why few pieces of the genre survived, evaluate possible intersections between guitar and around the period in question, as well as analyze how the musical imbrications and the terminological permeability that surrounded the period of the constitution of choro are also present in the subtitles and musical content of the pieces raised. Finally, we present the criteria that guided an imminent modern edition of the scores, to be published in partnership with the Legato publishing house. As a result, we believe that the discussion of such perspectives not only contributes to broaden the understanding of our past practices, but also enables new pieces of the pioneer repertoire of the Brazilian guitar to be gradually incorporated into the literature of the instrument.
Keywords: Guitar repertoire; Pioneer Choros; Circus and guitar; Polka and choro; Music edition for guitar